Systematic approach for dissecting promoters and designing transform systems in microalgae - Qinhua Gan; Xinjun Yu; Xiang Jiang; Xingwei Huang; Yi Xin; Yandu Lu (Microbial Cell Factories)
Abstract The rapidly expanding catalog of sequenced genomes has revolutionized the pace and scale of microalgal cellular metabolism delineation. However, knowledge of the gene regulation in these genomes is lacking. This is true even for Chlamydomonas reinhardtii, the laboratory model species where transcriptional regulation is best understood, although systematic knowledge of regulatory elements (e.g., promoters) remains elusive. This leads to limitations in microalgae for engineering system designs, which currently rely mainly on characterizing the molecular mechanisms of individual regulatory sequences via low-throughput methods. Here, we take a first step toward multi-promoter dissection and demonstrate systematic dissection of multiple microalgal promoters through quantitative genome-wide comparisons and sequence-based structural annotations. We demonstrate this approach on both well-studied and previously uncharacterized promoters in the oleaginous microalga Nannochloropsis oceanica IMET1. Using in silico design, representative regulatory elements were synthesized and assembled as building blocks for transgene circuits. Assessment of the in vivo activity revealed the maximum transformation efficiency (414 ± 102 transformants/µg DNA) in the plasmid pHN5-2 containing lhp promoter and α-tub terminator. Therefore, the present synthetic approach for establishing engineering systems is superior to the conventional empirical methods. Applying these transforming circuits to the creation and characterization of a gene-indexed loss-of-function mutagenesis library verifies the applicability of this strategy to the discovery and standardization of regulatory parts for microalgae. Moreover, the generality of the approach presented here provides the possibility of quantitative promoter dissection and rational transform system design in N. oceanica and a wide range of other microalgae.